A Self‐Enhancing Nanoreactor Reinforces Radioimmunotherapy by Reprogramming Nutrients and Redox Metabolisms. (27th January 2023) - Hou, Mengfei; Su, Haiyang; Wu, Qinghe; Sun, Wenshe; Zhang, Pengli; Jiang, Yifei; Qian, Kun; Zhang, Chunfu
Abstract: Altered metabolism of cancer cells reshapes the unique tumor microenvironment (TME) with glucose addiction and high antioxidant levels, resulting in a strong alliance to promote tumor progression and treatment failure. Herein, a Pd/Pt/Au tri‐metallic mesoporous nanoparticle coated with pH‐responsive tannic acid‐iron ion (Fe III TA) network (PdPtAu@TF) is fabricated, aiming at reinforcing radioimmunotherapy by reprogramming nutrients and redox metabolisms. PdPtAu@TF has a fine hierarchical structure and demonstrates high glucose oxidase, peroxidase‐, catalase‐ and glutathione peroxidase‐mimic activities, acting as a self‐enhancing nanoreactor to consume endogenous glucose and break redox homeostasis in the harsh TME. As a result, cancer cells accelerate the uptake of lipids, especially polyunsaturated fatty acids when glucose is deficient, and then fall into lipid peroxidation‐induced ferroptosis trap to sensitize radiotherapy (RT), inhibiting tumor progression. More significantly, combined treatment with PdPtAu@TF can promote the polarization of pro‐inflammatory M1‐type macrophages as well as inhibit the proliferation of cancer‐associated fibroblasts to overcome RT‐induced immunosuppression and eliminate excessive tissue fibrosis, thereby eliciting antitumor immunity and suppressing tumor metastasis. Consequently, this study describes a promising strategy to enhance the efficacy of radioimmunotherapy by reprogramming tumor nutrients and redox metabolisms, which has great potential to benefit cancer treatments. Abstract : The Pd/Pt/Au tri‐metallic mesoporous nanoparticles (PdPtAu@TF) exhibit high glucose oxidase‐, peroxidase‐, catalase‐ and glutathione peroxidase‐mimic activities and can function as a self‐enhancing nanoreactor to consume glucose and break redox homeostasis in the harsh tumor microenvironment. This study provides a promising strategy to enhance the efficacy of radioimmunotherapy by reprogramming tumor nutrients and redox metabolisms.